Medium-term clinical efficacy and safety of single incision and modified trans-obturator mid-urethral slings for female stress urinary incontinence - Jerome Melon; Päivi K. Karjalainen; Claire McGannon; Joseph K. Lee; Anna Rosamilia (BMJ Publishing Group, 2022)
Aims: To evaluate the medium term efficacy and safety of Altis and Solyx single incision slings (SIS) compared with tension-free vaginal tape (TVT) Abbrevo trans-obturator sling. We hypothesize that both SIS show little difference in efficacy and safety and perform similarly to TVT Abbrevo. Methods: We conducted an ambispective comparative cohort study of women with stress urinary incontinence who received a SIS in comparison to matched TVT Abbrevo subjects from a concurrent randomized controlled trial (RCT). Subjects were identified retrospectively, and prospectively invited for examination and questionnaires>12 months post-operatively. Exclusions included intrinsic sphincter deficiency, previous sling surgery, and others. Primary outcome was subjective cure [negative response to International Consultation Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF) question 6, leakage during coughing/activity]. Secondary outcomes include objective cure (negative cough stress test), functional outcomes, and adverse events. Results: Between 2012 and 2018, a total of 113 women received one of two SIS surgeries; Solyx (n ​= ​50) followed by the Altis (n ​= ​63); 104 were available for final efficacy analysis. Mean follow-up was 21.7 (Altis), 46.0 (Solyx), and 29.0 (Abbrevo) months. Baseline characteristics were comparable between the groups. There was no significant differences in the subjective or objective cure rates between the groups, and no differences in functional outcomes such as patient global impression of improvement, and post-operative ICIQ-UI SF score. There was a low rate of mesh related complications and no differences seen between the groups. Conclusions: Despite being an underpowered study, Altis and Solyx SIS have favourable efficacy and safety profiles which are comparable to an established trans-obturator mid-urethral slings (MUS).